O‗zbekistonda aholiga xizmat ko‗rsatish sohalarini geografik jihatdan tadqiq etish tajribalari (SCIENCE and SOCIETY, 2024)
The article describes the geography of public service sectors in the Republic of Uzbekistan, its main directions, territorial and periodic features. In addition, the research conducted on the geography of public services, were analyzed content and essence of large monographic works.